Flow simulation in compressor cascades at high angles of attack - Терещенко, Юрий Матвеевич; Дорошенко, Екатерина Викторовна; Аболхассан, Джалал заде (Eastern-European Journal of Enterprise Technologies, 2015)
The research objective was to assess the possibilities of using the method of numerical simulation for calculating the aerodynamic characteristics of single-row and double-row of compressor cascades. The flow calculation is performed by the numerical solution of the Navier-Stokes equations, to close which the SST Menter turbulence model is used. The first stage was the flow calculation in the single-row compressor cascade. The flow calculation was held at the angle of attack i=0° and speed ratio λ=0.42-0.83. According to numerical experiment and physical experiment, the dependence of the total pressure loss coefficient and speed ratio was constructed. Calculations have shown that the calculation error is allowable (3.1-5.6%) and the possibility to use the numerical experiment with a given topology of the cascade, SST turbulence model and High resolution design scheme for further research. The second stage was a series of gas-dynamic calculations of the flow in the above compressor cascade for building aerodynamic characteristics. The calculations were performed at a fixed Mach number Mw1=0.72, the angle of attack varied from 0º to + 20º. At small angles of attack, the flow separation does not occur. At the angle of attack +20º for the given cascade, boundary layer separation occurs. The third stage was a series of calculations of geometrically equivalent double-row cascade for building aerodynamic characteristics. Comparison of aerodynamic characteristics of single-row and geometrically equivalent double-row compressor cascade in the field of the Reynolds self-similar modes (Re>105) at the Mach number Mw1=0.72 and angles of attack i=0º...20º, obtained using the numerical experiment has shown that double-row compressor cascades have a wider variation range of angles of attack of the unseparated flow. This finding is well consistent with the results of other authors. Thus, using the computational experiment allows to solve the problems of determining the efficiency of double-row blade rows.